Implemetasi Otonomi Daerah Tentang Perimbangan Keuangan Pusat dan Daerah - Suroso Imam Zadjuli (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2002)
This article is part of the research report of the writer on the perspective of region autonomy in the region budget finance. In this article, writer start the discussion about the problem of region autonomy with the present of ten Acts which were from the house representative of Indonesian Republic in 1999, which has the strong influence due to region economy. This article also research the problem that happen and ought to be solved by the coming of region autonomy and decentralization era, especially the writer stresses in finance aspect autonomy that is about the tax. As the conclusion of this article, the writer argues that infact the government does not master the real macro economy data and the house of representative does not understand well the function of the finance balance between the center government and the region.